A Cross-Cultural Study of Theory of Mind Using Strange Stories in School-Aged Children from Australia and Mainland China. Issue 1 (1st January 2022) - Wang, Si; Andrews, Glenda; Pendergast, Donna; Neumann, David; Chen, Yulu; Shum, David H. K.
ABSTRACT: To date, cross-cultural studies on Theory of Mind (ToM) have predominantly focused on preschoolers. This study focuses on middle childhood, comparing two samples of mainland Chinese ( n = 126) and Australian ( n = 83) children aged between 5.5 and 12 years. Strange Stories, the most commonly used measure of ToM, was employed. The study aimed to examine the one- versus two-factor structure and measurement invariance of Strange Stories across two cultures; use the verified invariant model of Strange Stories to compare children's cognitive and affective ToM across two cultures; and finally, to investigate correlates of individual differences on Strange Stories cross-culturally. Multiple-groups confirmatory factor analysis revealed the measurement invariance of a two-factor model of Strange Stories (cognitive and affective) in both groups. Chinese children performed comparably to Australian children on cognitive ToM stories, but more poorly than Australian children on affective ToM stories. There were cultural differences in the correlates of ToM. The number of older siblings was a positive predictor of cognitive ToM for Chinese children, but a negative predictor of cognitive ToM for Australian children. The findings confirm that Strange Stories is a reliable measure for evaluating ToM in school-aged children from mainland China and Australia and highlight the importance of considering both cognitive and affective aspects of ToM in cross-cultural comparison.